An organic management alternative that improves soil quality in cocoa plantations under agroforestry systems - Florida Rofner, Nelino (2022)
The organic management of Theobroma cacao in agroforestry systems is a viable alternative, which is being applied in the Alborada Estate under the name of Mendis Organic Management (MOM) in honor of the researcher and owner of the experimental area. The MOM technology integrates a set of techniques according to the physiological cycle of the plant such as drastic annual pruning, application of compost, foliar biofertilizer, and the use of a variety of cocoa with high planting density. Therefore, the research evaluated the effect of MOM management on soil quality with cocoa plantations (varieties CCN-51 and CMP-15), under agroforestry system developed in the Alborada farm, Leoncio Prado province, Huanuco, Peru. A completely randomized design (CRD) was carried out, the treatments were cocoa areas: CCN-51 of 2x2 m and 10 years of installation (MOM1), CMP-15 of 2x2 m and 4 years (MOM2), CMP-15 of 2x1 m and 5 years (MOM3), CMP-15 of 3x2 m and 13 years (MOM4). Soil physical and chemical indicators were evaluated. All indicators showed significant differences between treatments, the principal component analysis (PCA) considered relevant the sand fraction, clay, OM, N, Ca2+, Mg2+, K+ and CEC, the modeling shows a negative impact in MOM2 and significantly positive in MOM4, regardless of the variety and planting density, observing significant increases for pH, OM, N, P, Ca2+, Ma2+ and CEC. The work shows the great potential of MOM management as a technological alternative to improve soil quality in cocoa plantations under agroforestry systems.